Who Pays? Coverage Challenges for Cardiovascular Genetic Testing in U.S. Patients - Katherine Grace Spoonamore; Nicole M Johnson (Frontiers in Cardiovascular Medicine, 2016)
Inherited cardiovascular conditions are common, and comprehensive care of affected families often involves genetic testing. When the clinical presentations of these conditions overlap, genetic testing may clarify diagnoses, etiologies, and treatments in symptomatic individuals and facilitate the identification of asymptomatic, at-risk relatives, allowing for often life-saving preventative care. Although some professional society guidelines on inherited cardiac conditions include genetic testing recommendations, they quickly become outdated owing to the rapid expansion and use of such testing. Currently, these guidelines primarily discuss the benefits of targeted genetic testing for identifying at-risk relatives. Although most insurance policies acknowledge the benefit and necessity of this testing, many exclude coverage for testing altogether or are vague about coverage for testing in probands, which is imperative if clinicians are to have the best chance of accurately identifying pathogenic variant(s) in a family. In response to uncertainties about coverage, many commercial cardiovascular genetic testing laboratories have shouldered the burden of working directly with commercial payers and protecting patients/institutions from out-of-pocket costs. As a result, many clinicians are unaware that payer coverage policies may not match professional recommendations for cardiovascular genetic testing. This conundrum has left patients, clinicians, payers, and laboratories at an impasse when determining the best path forward for meaningful and sustainable testing. Herein we discuss the need for all involved parties to recognize their common goals in this process, which should motivate collaboration in changing existing frameworks and creating more sustainable access to genetic information for families with inherited cardiovascular conditions.